Mechanisms of Cotranslational Maturation of Newly Synthesized Proteins - Kramer, Günter; Shiber, Ayala; Bukau, Bernd (Annual review of biochemistry, 2019)
The timely production of functional proteins is of critical importance for the biological activity of cells. To reach the functional state, newly synthesized polypeptides have to become enzymatically processed, folded, and assembled into oligomeric complexes and, for noncytosolic proteins, translocated across membranes. Key activities of these processes occur cotranslationally, assisted by a network of machineries that transiently engage nascent polypeptides at distinct phases of translation. The sequence of events is tuned by intrinsic features of the nascent polypeptides and timely association of factors with the translating ribosome. Considering the dynamics of translation, the heterogeneity of cellular proteins, and the diversity of interaction partners, it is a major cellular achievement that these processes are temporally and spatially so precisely coordinated, minimizing the generation of damaged proteins. This review summarizes the current progress we have made toward a comprehensive understanding of the cotranslational interactions of nascent chains, which pave the way to their functional state.
First published on December 3, 2018
Gesehen am 28.10.2019